2008
DOI: 10.3852/07-074r1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships ofPhytophthora andina, a new species from the highlands of Ecuador that is closely related to the Irish potato famine pathogenPhytophthora infestans

Abstract: Phylogenetic relationships of Phytophthora infestans sensu lato in the Andean highlands of South America were examined. Three clonal lineages (US-1, EC-1, EC-3) and one heterogeneous lineage (EC-2) were found in association with different host species in genus Solanum. The EC-2 lineage includes two mitochondrial (mtDNA) haplotypes, Ia and Ic. Isolates of P. infestans sensu lato EC-2 fit the morphological description of P. infestans but are different from any genotypes of P. infestans described to date. All iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 54 publications
6
43
0
1
Order By: Relevance
“…uniformis and P. alni subsp. multiformis [31][33], P. andina with P. infestans as one parent [34][36], P. × serendipita ( P. cactorum × P. hedraiandra ) [29], [37], four hybrids in subclade 6b: P. amnicola × P. taxon PgChlamydo (A-PG), P. taxon PgChlamydo× P. amnicola (PG-A), P. thermophila × P. amnicola (T-A), and P. thermophila × P. taxon PgChlamydo (T-PG) [38], as well as three hybrids in subclade 8b: P. porri × P. taxon parsley, P. porri ×a P. primulae -like species, and a third hybrid with two unknown species as parents [39]. It is interesting to note that parents of most individual hybrids belong to the same Phytophthora clade.…”
Section: Introductionmentioning
confidence: 99%
“…uniformis and P. alni subsp. multiformis [31][33], P. andina with P. infestans as one parent [34][36], P. × serendipita ( P. cactorum × P. hedraiandra ) [29], [37], four hybrids in subclade 6b: P. amnicola × P. taxon PgChlamydo (A-PG), P. taxon PgChlamydo× P. amnicola (PG-A), P. thermophila × P. amnicola (T-A), and P. thermophila × P. taxon PgChlamydo (T-PG) [38], as well as three hybrids in subclade 8b: P. porri × P. taxon parsley, P. porri ×a P. primulae -like species, and a third hybrid with two unknown species as parents [39]. It is interesting to note that parents of most individual hybrids belong to the same Phytophthora clade.…”
Section: Introductionmentioning
confidence: 99%
“…Alleles and mitochondrial haplotypes of this population had not been previously reported for other worldwide populations, which supports this explanation. EC-1 clonal lineage coexists with EC-3 in the same region and are the dominating populations on crops of Solanum tuberosum and Solanum lycopersicum (Gomez-Alpizar et al, 2008, Oliva et al, 2010Cardenas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, species-specific primers based on the ITS sequences are unable to differentiate closely related species. Gomez-Alpizar et al [24] and Kroon et al [25] reported that P. infestans , P. phaseoli , P. ipomoeae , P . sp.…”
Section: Resultsmentioning
confidence: 99%